Puppets and Protection: The Impact of Puppet-Based Videos on Teaching Pre-schoolers About COVID-19 - Domingo, Esther G.; Merida, Zeñorina C.; Tolentino, Salome B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The UNICEF’s Annual Report 2020 stressed the profound effect of the pandemic on the lives of children. When schools closed indefinitely and they lost access to many vital services, their felt anxious and unsettled (UNICEF, 2021). Young children are most vulnerable. To be able to protect them, they must be given accurate information on COVID-19. Although information about this infectious disease abound, they are mostly intended for adults. Hence, the need to design an informative material that is suitable for young children. Following the ADDIE model, the researchers designed a puppet video consisting of three episodes presented using the Filipino language that focused mainly on COVID-19 awareness and precautions. Forty-two pupils, 32 teachers, and 17 parents from three Day Care Centers participated in the study. The pupils were tested before and after watching the videos. Results show a statistically significant improvement in awareness, with the average score increasing by 0.43 points (from 14.41 to 14.83). The change is unlikely to be caused by random chance (p < 0.018), signifying the effectiveness of the material in improving COVID-19 awareness. Likewise, the teachers and parent-participants found the video highly effective in enhancing their children’s awareness of the dreaded disease. This study proves that a well-prepared, interesting, and highly informative technology-enhanced instructional material can be an effective method of raising awareness about health and social issues among very young children.